On the Need of User-deﬁned Libraries in OCL - Baar, Thomas (Electronic Communications of the EASST, 2011)
Reuse is a fundamental concept of efﬁcient software development. Object-oriented implementation languages offer reuse on different levels of granularity:method, class, library. While encapsulation of implementation code within methods and classes enables reuse within a project, user-deﬁned libraries are widely used toshare implementation code among different projects.The speciﬁcation language OCL offers language concepts like deﬁned attributes and deﬁned operations to enable reuse within a project. However, reuse among differentprojects is not possible since OCL does not support the concept of user-deﬁned libraries. There is no standardized way to import user-deﬁned OCL constraints intoanother project. In this paper, we argue on the need of a standardized mechanism to make reuse of OCL speciﬁcations within a different context possible.